A retrospective cohort study of tubal occlusion or salpingectomy for permanent contraception in Australia. (27th October 2021) - Baltus, Tanja; Brown, James; Kapurubandara, Supuni
Abstract : Background: Laparoscopic permanent contraception was previously accomplished most commonly using tubal occlusion procedures. Bilateral salpingectomy (BS) has recently been introduced as an alternative due to possibly superior contraception and greater protection against ovarian cancer. Aims: The aim of this study is to assess uptake, feasibility and perioperative outcomes of laparoscopic BS as an alternative to tubal occlusion in Australia. Materials and Methods: A retrospective review of permanent female contraception at two Australian hospitals from January 2014 through December 2020 was performed. The primary outcome was the uptake of BS. Secondary outcomes were feasibility, procedure length, number of ports, perioperative complications and admission length. Results: A total of 414 women were included; 92 (22.2%) underwent BS and 322 (77.8%) underwent tubal occlusion. There was a slow uptake of BS from 2014 to 2016 (0–3.2%), with a steep uptake from 2017 to 2020 (30–72%) ( P = 0.001). Procedure feasibility was 96.8% (62/64) and 99.3% (282/284) for BS and tubal occlusion group, respectively ( P = 0.64). BS procedure time was longer by 23 min ( P < 0.001). Three or more surgical ports were used in all cases of BS compared to 4.5% of the tubal occlusion group ( P < 0.001). There were no intraoperative complications. There were nine and six postoperative complications in the tubal occlusion versus BS group, respectively ( P = 0.10). The median admission length was 7.1 (tubal occlusion) versus 7.3 (BS) h ( P = 0.10), with five unintended overnight admissions. Conclusion: BS is an increasing choice for permanent contraception. It appears equally feasible as tubal occlusion but typically requires a longer procedure time and a minimum of three surgical ports.